History of the Umayyads’ Attention to Markets for the Improvement of Economic and Social Life (41-125 AH/661-742 AD) - Al-Qaddar, Bashara Abdullah; Bashinah, Mohammed Omar (The annual Scientific Conference for Under and Postgraduate Students at the University., 2024)
The research presents various models of markets during the Umayyad era, focusing on their economic and social impacts. It addresses how markets were organized and the diversity of available goods, highlighting their role in enhancing both internal and external trade. The research demonstrates that markets were vital centers for cultural and social interaction, contributing to changes in social relationships and enhancing the role of women in commerce. Additionally, it discusses the impact of markets on urban growth and infrastructure development. The aim of the research is to study how markets were organized and their role in boosting the Umayyad economy, exploring their effects on social life and human relations, classifying different types of markets during the Umayyad period, such as local and international markets, and providing insights into how these markets shaped the economic and social identity of Umayyad society. The researchers relied on a historical narrative analytical approach as much as possible, following the APA style. The research yielded several key findings, including that markets remained without defined structures or roofs until the Umayyad era, making the Umayyads the first to construct independent buildings for markets. It also confirmed the attention of Umayyad caliphs and their officials to standardize measures and weights as a form of market regulation. The roles of market overseers varied and evolved with the expansion of the Arab Islamic state during the Umayyad period. Furthermore, the markets exhibited significant growth in trade movement, contributing to economic enhancement and developing urban infrastructure, such as roads and public facilities, which facilitated trade and transportation.